Preparation and use of SER/GLU-based DES as a novel and potent catalyst for the green synthesis of pyrazolopyranopyrimidines - Nastaran Dehnokhalaji; Davood Habibi; Arezo Monem; Afagh Ranjbaran (Scientific Reports)
Abstract Based on the eutectic point phase diagram, a novel natural deep eutectic solvent (SER/GLU-DES) was prepared by a mixture of one mole of serine (SER) and one mole of glutaric acid (GLU), and characterized by various techniques. Then, it was used as a novel and potent catalyst for the synthesis of two sets of biologically important pyrazolopyranopyrimidines via a one-pot four-component condensation reaction of ethyl acetoacetate, hydrazinehydrate/ phenylhydrazine, barbituric acid and aldehydes at 70 °C, in solvent-free conditions.